Historical trends and variability of temperature extremes in two climate vulnerable regions of Bangladesh (Journal of the Bangladesh Agricultural University, 2018)
Research on temperature extremes deserves more importance because it reacts sensitively to climate change. As elsewhere across the world, Bangladesh has already become a victim of temperature extremes. Hence, this study was conducted to assess the trends and variability of 11 temperature-related extreme indices based on daily maximum (TX) and daily minimum (TN) temperature recorded at Rajshahi and Barisal over the period 1976–2015. The indices were calculated on annual basis and their average annual and decadal trends were evaluated by non-parametric Mann-Kendall test and Sen’s slope estimate. Significant (p ≤ 0.01) upward trend was observed in some of the hot extremes, such as SU35: number of days with TX > 35°C and TR25: number of days with TN > 25°C, indicating that the number of days and nights with extreme hot temperature are increasing in both sites. Significant decreasing rate (-0.308 day/year) of SU25: number of days with TX > 25°C and increasing rate (1.00 day/year) of SU35 demonstrate that moderate hot days are converting to extreme hot days at Rajshahi. All cold indices showed significant (p ≤ 0.05) variations at Rajshahi implying that cold extremes are becoming severe in this area. Significant rising trend of diurnal temperature range (DTR) indicated the higher rate of increase in TX than in TN at Rajshahi. The increasing trend of all hot indices at Barisal, close to the coast, reveals more warming in hot extremes. However, no significant trends of cold indices were observed at Barisal. Significant average decadal variations of temperature indices were only observed for hot index TNx: annual maximum TN (0.372 °C/decade) and cold index CD25: number of days with TX < 25°C (4.70 days/decade) at Rajshahi and hot index SU35 (5.650 days/decade) at Barisal. So, the relatively dry western region of the country is vulnerable to both hot and cold extremes, whereas coastal area is susceptible to only hot extremes.J. Bangladesh Agril. Univ. 16(2): 283-292, August 2018